Verification of Model Transformations - Schätz, Bernhard (Electronic Communications of the EASST, 2010)
With the increasing use of automatic transformations of models, the correctness of these transformations becomes an increasingly important issue. Especially for model transformation generally defined using abstract description techniques like graph transformations or declarative relational specifications, however, establishing the soundness of those transformations by test-based approaches is not straight-forward. We show how formal verification of soundness conditions over such declarative relational style transformations can be performed using an interactive theorem prover. The relational style allows a direct translation of transformations as well as associated soundness conditions into corresponding axioms and theorems. Using the Isabelle theorem prover, the approach is demonstrated for a refactoring transformation and a connectedness soundness condition.